Designing School Tables and Chairs based on Anthropometry of Elementary School Students in Surabaya - Riska Ayu Yulianingtyas; Dani Nasirul Haqi (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: School tables and chairs are needed amongst many other facilities which support the teaching and learning activities. Uncomfortable tables and chairs can cause health problems. The purpose of this study is to design school table and chair sizes in accordance with anthropometry of elementary school students, so the tables and chairs do not cause health problems for children. Methods: The population used in this study was 72 students of elementary school students in Surabaya, and the sample size was 61 students. The sampling method used in this research was a simple random sampling. The anthropometric data measured were shoulder height in the sitting position, elbow height in the sitting position, popliteal-buttock length, knee height, popliteal height, shoulder width, and distance from elbow to fingertips. Meanwhile, the dimensions of tables and chairs measured were chair height, chair width, back length, back height, table height, table width, and underneath desk height. Results: The results of the research show that the sizes of existing tables and chairs are mismatched with student anthropometry. There are 7 dimensions of proposed table and chair sizes which are based on anthropometric data. Specifically, the chair height is 33.25 cm, chair width is 33.25 cm, backrest length is 46.50 cm, backrest height is 49.60 cm, table height is 56.85 cm, table width is 39.05 cm, and underneath desk height is 47 cm. Conclusion: The sizes of existing tables and chairs still need improvement in all dimensions based on the students’ anthropometric measurements.Keywords: anthropometry, chair, elementary school students, table